Correcting Measurements of Launch Vehicle’s Angular Motion Parameters of a Strapdown Inertial Navigation System with the Use of a Celestial Navigation System - GOLUBEK , O. (Science and Innovation, 2024)
Introduction. One of the tasks of developing strapdown inertial navigation systems with microelectromechanical sensors of launch vehicles is to ensure stringent requirements for the accuracy in determining the linear and angular motion with a guarantee of the successful completion of the satellite injection mission. parameters of launch vehicle’s strapdown inertial navigation system built with the use of microelectromechanical sensors. One of the ways to compensate for this degradation is the integrated use of inertial and celestial navigation systems. Purpose. The purpose is to increase the satellite injection accuracy by launch vehicle using a strapdown inertial navigation system with microelectromechanical sensors due to a celestial navigation system with star tracker. Material and Methods. Development of Kalman fi lter providing an integrated processing of measurements of angular motion parameters of a launch vehicle by a strapdown inertial navigation system and a star tracker. Statistical modelling of launch vehicle flight under the infl uence of various stochastic disturbances. Statistical processing of modelling results. Analysis of the proposed solution eff ectiveness. Results. A workable mathematical model for correcting measurements of angular motion parameters of launch vehicle with the use of a Kalman fi lter has been developed. Its performance has been tested by the example of a launch vehicle injection into a sun synchronous orbit 700 km high with the use of a two-pulse injection scheme. It has been demonstrated that the proposed solution makes it possible to improve the accuracy of the angular orientation up to 90% and the satellite injection up to 5% in terms of altitude and orbit inclination. Conclusions. The proposed development can be used to build navigation systems for advanced launch vehicles.